2005
DOI: 10.1152/ajpheart.01042.2004
|View full text |Cite
|
Sign up to set email alerts
|

GH-releasing peptides improve cardiac dysfunction and cachexia and suppress stress-related hormones and cardiomyocyte apoptosis in rats with heart failure

Abstract: . GH-releasing peptides improve cardiac dysfunction and cachexia and suppress stress-related hormones and cardiomyocyte apoptosis in rats with heart failure. Am J Physiol Heart Circ Physiol 289: H1643-H1651, 2005. First published June 10, 2005; doi:10.1152/ajpheart.01042.2004.-Growth hormone (GH)-releasing peptides (GHRP), a class of synthetic peptidyl GH secretagogues, have been reported to exert a cardioprotective effect on cardiac ischemia. However, whether GHRP have a beneficial effect on chronic heart fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 53 publications
2
58
0
2
Order By: Relevance
“…8) Hexarelin, a synthetic analog of ghrelin, shows effects similar to those of ghrelin and is more chemically stable, making it a potential alternative to ghrelin. Its beneficial action on the cardiovascular system has been reported by a lot of research, including inhibition of cardiomyocyte apoptosis, [9][10][11] anti-atherosclerosis, 12,13) improving cardiac output, [14][15][16][17] and suppressing cardiac fibrosis. 18) These effects are considered to be mediated not only by GHSR1a but also by activation of cardiac CD36 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…8) Hexarelin, a synthetic analog of ghrelin, shows effects similar to those of ghrelin and is more chemically stable, making it a potential alternative to ghrelin. Its beneficial action on the cardiovascular system has been reported by a lot of research, including inhibition of cardiomyocyte apoptosis, [9][10][11] anti-atherosclerosis, 12,13) improving cardiac output, [14][15][16][17] and suppressing cardiac fibrosis. 18) These effects are considered to be mediated not only by GHSR1a but also by activation of cardiac CD36 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t 13 It has been reported that increased levels of endogenous ghrelin during the progression of doxorubicin-induced cardiomyopathy and heart failure might provide a compensatory self-protective mechanism (Xu et al, 2005). The pathways responsible for this protective effect were investigated in vitro on primary cultured cardiomyocytes challenged with doxorubicin in the presence or absence of ghrelin or a TNF-α antagonist (Xu et al, 2005).…”
Section: Page 13 Of 27mentioning
confidence: 99%
“…The pathways responsible for this protective effect were investigated in vitro on primary cultured cardiomyocytes challenged with doxorubicin in the presence or absence of ghrelin or a TNF-α antagonist (Xu et al, 2005). Ghrelin not only reduced apoptosis and markers of oxidative stress, but also increased antioxidative enzyme activity and retained mitochondrial membrane potential and energy metabolism.…”
Section: Page 13 Of 27mentioning
confidence: 99%
See 1 more Smart Citation
“…The dosage and duration of Hex treatment (100μg/kg) was applied according to a previous study [266]. Therefore, administration of Hex commenced at week 4 after STZ induction for a subsequent two weeks.…”
Section: Chapter Three -Effect Of Hex On Metbolism Of Animals With/wimentioning
confidence: 99%